(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This research paper delves into the dynamic phenomenon of English neologisms, analyzing their core concept, types, and areas of appearance. Using a qualitative, descriptive methodology, it categorizes neologisms into eight major types, including blending, compounding, affixation, and semantic shift. The paper highlights how modern neologisms often originate from domains such as technology, social media, global events, and sociopolitical movements. These new lexical items not only expand the language but also reflect the cultural, technological, and ideological shifts of contemporary society. Ultimately, the study emphasizes the significance of neologisms in capturing the evolving nature of human communication in the digital age.